BUSINESS GAME AS ONE OF THE METHODS OF METHODOLOGY WORKS ON THE DEVELOPMENT OF CREATIVE STYLE ACTIVITIES OF TEACHER - N.V. Dudnichenko (Academy of Cognitive and Natural Sciences, 2004)
The point, the specificity, the ways, and the methods of organization of business games are based in this article during the methodical work like one of the forms of development of creative style in teacher's work.